Personal Factors as Predictors of Attitude Towards ICT Utilisation Among Lecturers of Students with Special Needs in Nigeria - Lazarus, Kelechi Uchemadu (The Center for Disability Studies and Services Brawijaya University, 2024)
Teaching students with special educational needs in higher institutions of learning, through the use of information and communication technology (ICT) facilities and equipment is beneficial to both the students and their lecturers. This study, therefore, investigates the contribution of lecturers’ personal factors (age, teaching experience, area of specialization and educational qualification) to the attitude of lecturers towards the use of ICT in teaching students with special educational needs in higher institutions of learning in Oyo State Nigeria. The descriptive research design was used, while the multi-stage sampling procedure was adopted for the study. There was a purposive selection of two institutions namely, the University of Ibadan and Federal College of Education (Special) Oyo, Oyo State, Nigeria. Using random sampling technique, 80 lecturers were selected from the two institutions. An adapted questionnaire on the attitudes of in-service teachers toward the use of the ICT was adopted for data collection. Data was analysed using frequency counts, percentages and multiple regression statistics. Demographic profiles revealed that the majority of the respondents were aged 44 years and above, highly experienced lecturers, Ph.D holders, special educators and from the non-science disciplines. The joint contribution of personal factors to lecturers’ attitude towards the use of ICT in teaching persons with special educational needs shows a multiple correlation R of 0.147 and a multiple R2 of 0.022. Also, the relative contributions of the independent variables to the dependent variable, expressed as beta weights, reveal: age (β = 0.02), teaching experience (β = 0.10), area of specialization (β = 0.07), and educational qualification (β = 0.03) respectively. The study concluded that the selected demographic variables are not significant predictors of lecturers’ attitude towards the use of ICT in teaching students with special educational needs in higher institutions of learning. It was recommended that all categories of lecturers, notwithstanding their demographics, should be encouraged to acquire more skills in the use of ICT tools for teaching their students with special educational needs and use these skills effectively for enhanced learning outcomes.